Updates and Advances: Pediatric Musculoskeletal Infection Imaging Made Easier for Radiologists and Clinicians - Furman, Michael S.; Restrepo, Ricardo; Kritsaneepaiboon, Supika; Laya, Bernard F.; Plut, Domen; Lee, Edward Y. (Seminars in Musculoskeletal Radiology, 2021)
Infants and children often present with a wide range of musculoskeletal (MSK) infections in daily clinical practice. This can vary from relatively benign superficial infections such as cellulitis to destructive osseous and articular infections and life-threatening deep soft tissue processes such as necrotizing fasciitis. Imaging evaluation plays an essential role for initial detection and follow-up evaluation of pediatric MSK infections. Therefore, a clear and up-to-date knowledge of imaging manifestations in MSK infections in infants and children is imperative for timely and accurate diagnosis that, in turn, can result in optimal patient management. This article reviews an up-to-date practical imaging techniques, the differences between pediatric and adult MSK infections, the spectrum of pediatric MSK infections, and mimics of pediatric MSK infections encountered in daily clinical practice by radiologists and clinicians.
Keywords: musculoskeletal; infection; pediatric; magnetic resonance imaging; ultrasound